A Comparative Study of Discursive Space in ritual structure and forms of the Cinematic based on Gilbert Doran's theory of Mythocritique in Lament of the Snow - Fereshteh Paidar Nobakht; Minoo Khany (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
The current research examines the relationship between form in cinema and the structure of ritual and archetypal systems based on Gilbert Doran's method of myth analysis. The main issue is how the creative forces of imagination and perception interact with visual forms. It is assumed that these processes, as kinds of aesthetic functions of cinema, are already involved with fixed, static and archetypal patterns, and the act of watching creates a mixed and interwoven space of aligned and opposite forces. This space, on one hand, is involved with external structures such as social systems and cosmologies of spectators, and on the other hand, is connected with internal systems such as archetypes, symbols, moral values ​​and beliefs. This research has developed a theoretical framework drawing on a descriptive and analytical method. Reflections on the film Lament of the Snow show that the formic aesthetic functions transform these relationships into a mixed and fluid space in which values ​​and concepts are created anew.